LISTENING MATERIAL IN THE 2013 CURRICULUM ENGLISH TEXTBOOK: WHAT DO THE TEACHERS THINK? - Dwi Oktalia; N. Ngadiso; Slamet Supriyadi (Universitas Sembilanbelas November Kolaka, 2018)
Listening is considered as the basic skill in learning a language. Listening lets students gain input in the form of audio. Due to the 2013 curriculum, schools are provided with English textbook prepared by the government. This textbook is used for the listening input which may affect the output of listening process. Therefore, the researchers are interested in conducting a research related to the weaknesses of the K13 English textbook When English Rings a Bell. The researchers want to know the weaknesses of the listening material in the textbook which can be known from the teachers’ perception. This research used qualitative and quantitative method. The instruments of this research are observation, questionnaire, and interview. The result of the study shows that there are several weaknesses of the listening material existing in the K13 English textbook. These weaknesses may affect to the output of language learning and cannot develop students’ listening skill. Therefore, it is expected that the government would take more attention on the listening material for students to help them better input for listening activity.